Analysis of the impact of electronic medical record types on continuity of care at community health centers - Fajar Yunita Sari; Selfi Handayani; Ratih Puspita Febrinasari; Vitri Widyaningsih; Arsita Eka Prasetyawati (Poltekkes Kemenkes Bandung, 2026)
Background: Continuity of care (CoC) is a key indicator that emphasizes the therapeutic relationship, service coordination, and continuity of information. Implementing EMR is expected to improve CoC, and the implementation of CoC can be influenced by aligning people, organizations, technology, and digital workloads. Objective: to analyze the impact of EMR type on continuity of care and assess the role of HOT-Fit factors and digital workload in community health centers. Methods: This study used an analytical, observational, cross-sectional design, involving 198 health workers from eight community health centers in Tasikmalaya City who use the ePus Klaster and Medisy systems. Respondents from nine professions were selected through multistage sampling. Data were collected using structured, reliable, and validated questionnaires based on the concepts of continuity of care, HOT-Fit, and cognitive workload (Cronbach’s alpha ≥0.70). The data were analyzed using bivariate and multivariate tests, including linear and logistic regression analyses. Results: Multivariate analysis shows that technology is the strongest predictor with the highest odds of increasing continuity of care across all dimensions, with results regarding informational continuity (β=0.51; p<0.001); (aOR=143.3; 95% CI=10.51–1954.2), relational continuity (β=0.53; p<0.001); (aOR=162.5; 95% CI=12.9–2035.3), and management continuity (β=0.48; p<0.001); (aOR=333.1; 95% CI=15.1–7343.8). Conclusion: Continuity of care is more influenced by technological and organizational factors than by the type of electronic medical record system itself. Therefore, strengthening technological capacity, organizational readiness, digital literacy, and the alignment of EMR systems with clinical workflows, rather than focusing solely on EMR adoption.